2008
DOI: 10.1093/ajcn/87.3.778
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract ingestion, fat oxidation, and glucose tolerance in healthy humans

Abstract: Acute GTE ingestion can increase fat oxidation during moderate-intensity exercise and can improve insulin sensitivity and glucose tolerance in healthy young men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
211
5
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(238 citation statements)
references
References 21 publications
18
211
5
4
Order By: Relevance
“…Since MCP-1 is a major chemoattractive chemokine for macrophage, it could be assumed that its reduction is probably related to the reduction in macrophage and oral glucose tolerance test were similar in both groups, independently of white tea intake. This result is in agreement with most studies on glucose homeostasis (NOMURA et al, 2008;VENABLES et al, 2008) after green tea intake. In those studies, in which a beneficial effect of green tea in reducing glucose was observed, the amount of green tea in the diet was about 3%, six times higher than that offered in the present study (KHAN et al, 2007), and the experimental period was 16 weeks, twice as much time of the present study (BOSE et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Since MCP-1 is a major chemoattractive chemokine for macrophage, it could be assumed that its reduction is probably related to the reduction in macrophage and oral glucose tolerance test were similar in both groups, independently of white tea intake. This result is in agreement with most studies on glucose homeostasis (NOMURA et al, 2008;VENABLES et al, 2008) after green tea intake. In those studies, in which a beneficial effect of green tea in reducing glucose was observed, the amount of green tea in the diet was about 3%, six times higher than that offered in the present study (KHAN et al, 2007), and the experimental period was 16 weeks, twice as much time of the present study (BOSE et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…It also may promote the phosphorylation of insulin-signaling proteins and enhance insulin activity. [20][21][22] Wolfram et al 23 indicated that EGCG beneficially improved glucose and lipid metabolism in H4IIE cells and enhanced glucose tolerance in models of diabetes. Green tea extract also could increase fat metabolism and lipolysis in healthy humans.…”
Section: Introductionmentioning
confidence: 99%
“…Green tea extract also could increase fat metabolism and lipolysis in healthy humans. 22 Another study provided evidence that green tea promoted glucose metabolism in healthy humans and produced an antihyperglycemic effect in diabetic mice. 24 A population-based, case-control study by Polychronopoulos et al 25 reported that tea consumption could reduce levels of fasting blood glucose in nonobese elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cross-over placebo controlled study (Venables et al, 2008) reported an increase of fat oxidation by 17% after a supplement containing various green tea polyphenols and 366 mg EGCG (but not caffeine) compared with the control group. It is the first evidence that a single catechin, namely EGCG, has the potential to moderately affect fat oxidation.…”
Section: Prevention Of Metabolic Syndrome (Mets) and Cardiovascular Dmentioning
confidence: 99%